Speech Practice Effects on Bilingual Children's Fast Mapping Performance - Kan, Pui Fong; Sadagopan, Neeraja (Seminars in Speech and Language, 2015)
Learning a new word involves many subsystems and their interactions. The purpose of this study was to examine whether speech practice facilitates the subsequent fast mapping performance of bilingual preschool children. Participants were 18 typically developing preschoolers who learned Cantonese (L1) as a home language and English (L2) as a second language. Each participant was asked to repeat each of the four novel words after an auditory model (speech practice) before he or she was exposed to the novel word-objects in the subsequent fast mapping task. Significant speech practice and language effects on fast mapping production scores were found. These findings suggest a complex relationship between speech learning, fast mapping, and L1–L2 language skills. Our results suggest that clinical methods that facilitate bilingual children's production skills (e.g., repeat after a model) hold promise as a means of improving the initial stage of word learning in both languages.
Keywords: Fast mapping; speech practice; bilingual children; word learning